2006
DOI: 10.1097/00000542-200606000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Anesthetic Properties of Propofol Microemulsions in Rats

Abstract: Propofol microemulsions cause induction in rats similar to that from macroemulsions. The surfactant concentration and type markedly affect the spontaneous destabilization and anesthetic properties of microemulsions, a phenomenon suggesting a mechanism whereby dose-response relation can be selectively modified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 37 publications
1
23
0
2
Order By: Relevance
“…Like other phenolic compounds, propofol is a membrane irritant [6]. The DOI: http://dx.doi.org/10.21454/rjaic.7518.231.emf pain on injection has been linked to the free propofol drug concentration, or the amount of drug freely dissolved in blood [7,8]. After an injection of propofol, the free drug concentration local to the injection site is affected by two factors: the emulsified propofol begins to dissolve after injection into the blood [9], but the much more likely factor is the amount of propofol freely dissolved in the emulsion continuous phase immediately mixing with the bloodstream at the intravenous injection site.…”
Section: Introductionmentioning
confidence: 99%
“…Like other phenolic compounds, propofol is a membrane irritant [6]. The DOI: http://dx.doi.org/10.21454/rjaic.7518.231.emf pain on injection has been linked to the free propofol drug concentration, or the amount of drug freely dissolved in blood [7,8]. After an injection of propofol, the free drug concentration local to the injection site is affected by two factors: the emulsified propofol begins to dissolve after injection into the blood [9], but the much more likely factor is the amount of propofol freely dissolved in the emulsion continuous phase immediately mixing with the bloodstream at the intravenous injection site.…”
Section: Introductionmentioning
confidence: 99%
“…A nanoemulsão é caracterizada por ser transparente, incolor e termodinamicamente estável, com partículas medindo entre 10 e 50ηm (MOREY et al, 2006b). Os veículos nanoemulsionados são estéreis, apirogênicos, biocompatíveis, não irritantes e não hemolíticos (DATE & NAGARSENKER, 2008).…”
Section: Introductionunclassified
“…Sodium caprylate (C 8 fatty acid) has been shown to cause significant hemolysis at a concentration of 213 mM (19). Although the microemulsions reported by Morey et al (18) do not contain such a high concentration of sodium caprylate, blood compatibility and parenteral acceptability of sodium salts of C 8 , C 10 and C 12 fatty acids on long term administration have not been established. Ryoo et al (20) in another investigation have reported formulation of microemulsion based on the Solutol ® HS 15 and ethanol.…”
Section: Introductionmentioning
confidence: 99%